Kick-Ass 2 - Millar, Mark (Marvel/Icon, 2012)
Dave Lizewski, a teenage comic book enthusiast, has become the superhero known as Kick-Ass. His former ally, Red Mist, has decided to become a super villain. Now Red Mist and Kick-Ass will square off.